Primary Care for Older Adults Models and Challenges (Springer International Publishing, 2018)
This book provides a comprehensive and systematic state-of-the science review of major primary care delivery models, how they address specific needs of older adults, and available evidence for their efficacy. Written by experts in the field, this book explores the patient-centered medical home model (PCMH) in depth and dives into the complexities of the "medical neighborhood". It describes and analyzes primary care specifically directed toward special, complex populations, such as the Health Home for safety net patients with mental health needs, and intensive primary care for older adults. It reviews an array of primary care models related to dual eligible patients including the GRACE primary care consultation model and PACE models. It describes primary care with Advanced Practice Nurses and Physician Assistants and explores in-depth the massive effort within the VA to develop the Patient Activated Care Team (PACT), a VA form of the PCMH that also has several offshoots that address complex older veterans and veterans with severe mental illness. Finally, it illuminates rarely discussed primary care that occurs within the home and within long-term care. Throughout the entire book, experts navigate the workforce, care quality, and financing challenges of primary care for older adults. Primary Care for Older Adults is a valuable resource for clinicians, researchers, patients, caregivers and their advocates, and policy makers who have an interest in designing, promoting, and implementing high quality primary care for older adults.